2022 IFFAS Award for Excellence Winner: Minimally Invasive Chevron-Akin for Correction of Moderate and Severe Hallux Valgus Deformities. Issue 4 (November 2022) - Carvalho, Kepler; Baptista, Andre D.; Ferrarezi, Samai; Nunes, Gustavo A.; Mansur, Nacime SB; Netto, Cesar de Cesar; Johnson, A. Holly; Dalmau-Pastor, Miki
Category: Bunion; Midfoot/Forefoot Introduction/Purpose: The Minimally Invasive Chevron-Akin (MICA) technique has already demonstrated efficacy compared with other known surgical treatments for mild to moderate Hallux Valgus (HV) deformities. MICA combines percutaneous osteotomies with the benefits of modern rigid internal fixation. By minimizing soft-tissue disruption and allowing large translation of the metatarsal head up to 100%, surgeons have used this technique to address severe deformities as well. The study aim was to evaluate the radiographic parameters, clinical improvement, and potential complications in moderate to severe hallux valgus cases, operated using the MICA technique. Methods: This is a retrospective study conducted between January 2017 and December 2020, that included patients with moderate to severe HV, who underwent surgical correction using the MICA technique. The sample size calculation was based on the AOFAS questionnaire. Thus, to obtain the 0.8 power, including 70 cases in this study, was necessary. The AOFAS score and weight-bearing AP radiographic views for hallux valgus evaluation were applied pre-operatively, after a follow-up period of 6 months, after one year of follow-up, and after two years of follow-up. Visual Analogic Scale (VAS) was applied pre-operatively, after 1 year of follow-up, and after 2 years of follow-up. The following radiographic parameters were measured: metatarsophalangeal hallux valgus angle (HVA), distal metatarsal articular angle (DMAA), and intermetatarsal angle (IMA) between the first and second metatarsals. To compare the measurements over time, Friedman's test was used. p<0.05 was considered to be statistically significant. Results: The average preoperative AOFAS score was 43.97 +- 17.89 and varied positively in the 6-month postoperative period, which was 90.17 +- 10.21 (p<0.01), maintained at 12 and 24 months. Preoperative VAS scores averaged 8.24 +- 1.51 and decreased to 1.37 +- 2.27 after 1 year and to 1.19 +- 2.23 after 2 years The initial IMA was 14.84 +- 3.57 degrees compared with a mean value of 8.1 +- 2.87 degrees (p<0.01) at six months and further decrease at 24 months postoperatively. The HVA showed a mean value of 30.37 +- 9.75 degrees preoperatively and 11.14 +- 6.8 degrees (p<0.01) at six months postoperatively, remaining stable in the postoperative evaluations at 12 and 24 months. The preoperative DMAA mean was 16.3 +- 8.55 degrees preoperatively and presented a significant drop (p<0.01) at the 6-months to 7.77 +- 5.44 degrees. Complications included painful hardware, neuropathic pain, and loss of correction. Conclusion: This study demonstrates that the MICA technique is a safe and effective procedure for correcting moderate to severe HV long-term, with a low rate of recurrence and severity of complications. Patients undergoing the surgical procedure in our series showed a significant reduction in radiographic parameters and a significant improvement in clinical scores, maintaining these results over time.The good results of this study justify the continued use of the technique and suggest the need to compare its results with other long-term studies and compare their effectiveness with open techniques.